EVALUASI PENGARUH CUACA TERHADAP KEANDALAN SISTEM DISTRIBUSI - Sunanda, Wahri (FORISTEK : Forum Teknik Elektro dan Teknologi Informasi, 2013)
System distribution has used 13 of loads with source of generation from substation. It will be simulated on EDSA Technical 2005 in bad weather that occur in system during one month. Probability of bad weather occurance is 8,33%/year with failure rate almost twice than normal condition, about 2000%. The result shows that weather contributes significant influence for reliability of distribution system although the bad weather happened in short time. Keyword : failure rate, reliability, distribution system.